2018
DOI: 10.3390/e20030199
|View full text |Cite
|
Sign up to set email alerts
|

Criticality Analysis of the Lower Ionosphere Perturbations Prior to the 2016 Kumamoto (Japan) Earthquakes as Based on VLF Electromagnetic Wave Propagation Data Observed at Multiple Stations

Abstract: Abstract:The perturbations of the ionosphere which are observed prior to significant earthquakes (EQs) have long been investigated and could be considered promising for short-term EQ prediction. One way to monitor ionospheric perturbations is by studying VLF/LF electromagnetic wave propagation through the lower ionosphere between specific transmitters and receivers. For this purpose, a network of eight receivers has been deployed throughout Japan which receive subionospheric signals from different transmitters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 43 publications
(66 reference statements)
5
44
0
Order By: Relevance
“…In Table 8.1 of Reference [ 6 ], one can find a compilation of 14 cases including a variety of dynamical models in which the condition = 0.070 has been ascertained (cf. this has been also later confirmed in the analyses of very recent experimental results in Japan by Hayakawa and coworkers [ 55 , 56 , 57 ]). Especially for the case of SES activities, it has been found that, when they are analyzed in natural time, we find values close to 0.070 ([ 35 , 36 , 38 , 39 ], e.g., see Table 4.6 on p. 227 of Reference [ 6 ]), i.e., when analyzing in natural time the small EQs with magnitudes greater than or equal to a threshold magnitude that occur after the initiation of an SES activity within the selectivity map of the measuring station that recorded the SES activity, the condition is found to hold for a variety of a few days up to one week before the strong EQ occurrence [ 6 , 30 , 40 , 41 , 44 , 45 , 46 , 47 , 54 , 58 ] .…”
Section: Natural Time Analysis Backgroundsupporting
confidence: 71%
“…In Table 8.1 of Reference [ 6 ], one can find a compilation of 14 cases including a variety of dynamical models in which the condition = 0.070 has been ascertained (cf. this has been also later confirmed in the analyses of very recent experimental results in Japan by Hayakawa and coworkers [ 55 , 56 , 57 ]). Especially for the case of SES activities, it has been found that, when they are analyzed in natural time, we find values close to 0.070 ([ 35 , 36 , 38 , 39 ], e.g., see Table 4.6 on p. 227 of Reference [ 6 ]), i.e., when analyzing in natural time the small EQs with magnitudes greater than or equal to a threshold magnitude that occur after the initiation of an SES activity within the selectivity map of the measuring station that recorded the SES activity, the condition is found to hold for a variety of a few days up to one week before the strong EQ occurrence [ 6 , 30 , 40 , 41 , 44 , 45 , 46 , 47 , 54 , 58 ] .…”
Section: Natural Time Analysis Backgroundsupporting
confidence: 71%
“…[ 11 ], one can find a compilation of 14 cases in which the condition = 0.070 has been ascertained. (This was also later confirmed in the analyses of very recent experimental results in Japan by Hayakawa and coworkers [ 45 , 46 ].) In addition, natural time has been recently employed by Turcotte and coworkers [ 47 , 48 , 49 , 50 ] as a basis for a new method to estimate the current level of seismic risk.…”
Section: Natural Time Analysis Backgroundsupporting
confidence: 70%
“…NTA has found applications in a wide variety of fields ranging from cardiology (see, e.g., [12][13][14][15]) to statistical physics (see, e.g., [16][17][18][19][20][21]), and atmospheric science (see, e.g., [22][23][24]). One of the main applications of NTA, however, is the study of the physics of EQs (see, e.g., [25][26][27][28][29][30][31][32][33][34][35][36][37]). In addition, natural time is considered as the basis of the "nowcasting earthquakes" methodology that has been introduced recently [38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%